PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 41 DURI BARAT KECAMATAN MANDAU - Drawati, Drawati; Lazim N, Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted because of the low value of the results of social studies of fourth grade students of SDN 41 West Duri Bengkalis. Of the 25 students, the number of students who reached KKM only 11 (44%) students, and which does not achieve KKM 14 students (56%). with an average of 63.2 and is still below the minimum completeness criteria (KKM) is applied in schools is 70.00. The purpose of this study to improve student learning outcomes IPS IV SDN 41 West Duri Bengkalis with the application of problem-based learning. The results obtained by the average value of the basic score of 63.2 students at UH I decrease the average is 59.8 with a 5.38% decline in the percentage increase occurred in UH II with an average value of 71.2 with a percentage increase of 19% , Once applied problem-based learning model teacher in the first cycle to 24% classical completeness (not finished), on the second cycle increased to 80% completeness. So also with the activities of teachers in the first cycle to the second cycle increased by 35% from 60% to 95% with the category enough to be very good. As well as on the activities of students in the first cycle to the second cycle there was an increase of the total value of 11 to 17 with a percentage of 55% to 85% with the category enough to be very good.Key Words: Based Problems, Learning Outcomes IPS